Second-Generation Fiscal Rules : Balancing Simplicity, Flexibility, and Enforceability - Eyraud, Luc (Staff Discussion Notes; Staff Discussion Notes ;, 2018)
Fiscal rule frameworks have evolved significantly in response to the global financial crisis. Many countries have reformed their fiscal rules or introduced new ones with a view to enhancing the credibility of fiscal policy and providing a medium-term anchor. Enforcement and monitoring mechanisms have also been upgraded. However, these innovations have made the systems of rules more complicated to operate, while compliance has not improved. The SDN takes stock of past experiences, reviews recent reforms, and presents new research on the effectiveness of rules. It also proposes guiding principles for future reforms to strike a better balance between simplicity, flexibility, and enforceability. Read the blog.